EFFECTIVENESS OF THE PROBLEM BASED LEARNING MODEL ON CRITICAL THINKING ABILITY ABOUT SCIENCE SUBJECT FOR FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Nila Rahma Afriani (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the effectiveness of the model problem based learning on the science critical thinking skills of fifth grade elementary school students. This type of research is literature research. The data used in this study were obtained from the websites DOAJ, Sinta, and Google Scholar. Researchers use 30 articles that have been reduced according to the following criteria: (1) Articles published in the last 5 years, (2) reputable national or international articles, (3) Research in the form of experiments and classroom action research using Problem Based Learning, (4) The research population is elementary school students, and (5) The content of science, mathematics, or thematic subjects. Based on the results of the article analysis, it can be concluded that the model problem based learning can be applied in science and mathematics learning, the model problem based learning can improve various abilities and learning outcomes, and the model is problem based learning effectively applied in the fifth grade science learning to improve critical thinking skills. This research can be used as a benchmark for using models problem based learning in learning.